2023
DOI: 10.1111/ajd.13982
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cyclosporine and systemic corticosteroid for treating drug reaction with eosinophilia and systemic symptoms syndrome: A retrospective 20‐year single‐centre study in South Korea

Abstract: Background/Objectives: Drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome is a potentially life-threatening hypersensitive disorder.Cyclosporine has been indicated for adverse cutaneous drug eruptions. However, studies evaluating its clinical effectiveness in DRESS syndrome have been rare.This study aimed to evaluate the clinical efficacy of cyclosporine in DRESS syndrome compared to that of systemic corticosteroids. Methods:In the cyclosporine group, oral cyclosporine was administered twic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Evidence is based only on small retrospective case series. In the latter, IVIGs are either combined with systemic corticosteroid therapy in steroid-refractory cases or with cyclosporine as a first-line regimen . For IVIGs, toxic effects have been reported when these were used as single agents without corticosteroids in DRESS .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence is based only on small retrospective case series. In the latter, IVIGs are either combined with systemic corticosteroid therapy in steroid-refractory cases or with cyclosporine as a first-line regimen . For IVIGs, toxic effects have been reported when these were used as single agents without corticosteroids in DRESS .…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroids, as opposed to cyclosporine, are the standard of care in the treatment of DRESS syndrome. Therefore, this literature on cyclosporine in the treatment of DRESS syndrome has been limited to primarily small case reports, 1 case-control study with 5 patients treated with cyclosporine compared to 21 patients treated with corticosteroids [4], and 1 retrospective study with 27 patients treated with cyclosporine compared to 53 patients treated with corticosteroids [12]. The previous cases are summarized in the Multimedia Appendix 1 [2][3][4][5][6][7][8][9][10][11][13][14][15][16].…”
Section: Comparison With Prior Workmentioning
confidence: 99%
“…Data from the retrospective study are not included in the summary, as the data were aggregated and could not be separated into individual cases. The vast majority of these previous studies have suggested that cyclosporine is effective and may lead to rapid clinical resolution of DRESS syndrome [2][3][4][5][6][7][8][9][10][11][12]16]. In the case-control study, the patients treated with cyclosporine were found to have a shorter time to clinical resolution than those treated with corticosteroids [4].…”
Section: Comparison With Prior Workmentioning
confidence: 99%
See 2 more Smart Citations